2009
DOI: 10.1007/s00408-009-9175-1
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Association Between Asthma and ABO Blood Group

Abstract: ABO is the most important blood group system in transfusion and transplantation practices. Glycosyltransferases are controlled by the ABO system which is helpful in building oligosaccharide structures on the cell surface of erythrocytes and vascular endothelium and in the exocrine secretion system, including the respiratory tract. We analyzed the ABO blood group of 200 children and adults with asthma as well as that of 2000 healthy subjects as controls. The most common blood group among the patients and contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 6 publications
1
17
1
Order By: Relevance
“…Significantly higher prevalences of adult asthma were observed in Le-negative or non-secretor subjects of blood group O (4). On the contrary, a lack of association between asthma and the ABO system was found in the study conducted in India (11). In Brazil, the patients with allergic rhinitis and controls were compared according to the frequencies of the ABO phenotypes.…”
Section: Discussionmentioning
confidence: 92%
“…Significantly higher prevalences of adult asthma were observed in Le-negative or non-secretor subjects of blood group O (4). On the contrary, a lack of association between asthma and the ABO system was found in the study conducted in India (11). In Brazil, the patients with allergic rhinitis and controls were compared according to the frequencies of the ABO phenotypes.…”
Section: Discussionmentioning
confidence: 92%
“…(7) Associations between the ABO and Secretor systems and asthma have also been observed in Italian (8) and Taiwanese children (9) but not in Indian adults. (10) Despite these contradictory results observed among patients suffering from asthma, studies associating these genetic markers with allergic rhinitis are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Kauffmann [14] suggested that Lewis-negative or non-secretor with group O predispose to lower lung function and higher prevalence of The result is not significant at p < 0.05 The result is not significant at p < 0.05 The result is not significant at p < 0.05 wheezing and asthma. On the contrary, other publications reported no significant differences between asthma and any blood group in ABO [15,16]. Recently performed studies evaluating the relationship between ABO blood group status and allergic diseases have indicated a strong association with red meat allergy, and the B-negative blood groups after tick bites.…”
Section: Discussionmentioning
confidence: 87%